Water policy in Spain: a portrait - López C.; Martín I.; Alcácer C. (Water culture and water conflict in the Mediterranean area, 2008)
This work is a snapshot of the foundations and the basic lines of water policy in Spain. In a territory which is highly conditioned by the aridity of the climate and ongoing cycles of drought, traditional water policy has concentrated on the availability of the supply, especially for agricultural irrigation purposes, the economic driving force of a traditionally rural and relatively undeveloped country. The problems originated by a policy which met its objectives but which was no longer satisfactory have shown the need for a new orientation in water policy. A new discourse based on principles such as the environment, the concept of water as something more than just a commodity and participatory decision-making are all ideas which have taken on substance in the regulations through the approval of the new Water Framework Directive. Adaptation to the new European regulations, the modernization of Spanish irrigation systems, new water management in the urban cycle (supply and treatment), a risk policy based on planning and an environmental line of action are the new pillars of water policy in Spain.
1. MELIA Workshop Water Culture and Water Conflict, 2007/11/22-25, Nabeul-Médenine (Tunisia)